Comparative pharmacokinetics of rVIII‐SingleChain and octocog alfa (Advate®) in patients with severe haemophilia A. (19th July 2016) - Klamroth, R.; Simpson, M.; von Depka‐Prondzinski, M.; Gill, J. C.; Morfini, M.; Powell, J. S.; Santagostino, E.; Davis, J.; Huth‐Kühne, A.; Leissinger, C.; Neumeister, P.; Bensen‐Kennedy, D.; et al.
Abstract : Background: rVIII‐SingleChain, a novel recombinant factor VIII (rFVIII), has been designed as a B‐domain truncated construct with covalently bonded heavy and light chains, aiming to increase binding affinity to von Willebrand factor (VWF). Preclinical studies confirmed greater affinity for VWF, giving improved pharmacokinetic and pharmacodynamic properties compared with full‐length rFVIII. Aim: To investigate the pharmacokinetics of rVIII‐SingleChain and compare them against those of full‐length rFVIII. Methods: This study enrolled 27 patients with severe haemophilia A in the AFFINITY clinical trial programme. After a 4‐day washout period, all patients received a single infusion of 50 IU kg −1 octocog alfa (Advate ® ); after a ≥4‐day postinfusion washout period, they received a single infusion of 50 IU kg −1 rVIII‐SingleChain. Blood samples for pharmacokinetic assessments of each product were collected before infusion (predose) and at 0.5, 1, 4, 8, 10, 24, 32, 48 and 72 h postinfusion for both products. Results: rVIII‐SingleChain had a longer mean half‐life ( t 1/2 ) (14.5 vs. 13.3 h), lower mean clearance (CL) (2.64 vs. 3.68 mL h −1 kg −1 ), higher mean residence time (20.4 vs. 17.1 h) and larger mean AUCinf (2090 vs. 1550 IU?h dL −1 ) than octocog alfa, respectively. The mean AUCinf after rVIII‐SingleChain infusion was 35% larger than after octocog alfa. A similar pattern was observed for AUC0‐last . No serious adverse events or inhibitors were reported. Conclusions: rVIII‐SingleChain has a favourable pharmacokinetic profile compared with octocog alfa and was well tolerated. The prolonged t 1/2, larger AUC and reduced CL of rVIII‐SingleChain may permit longer dosing intervals, thereby improving patient adherence to prophylactic treatment.